Thermo-optic variable optical attenuators using plasmon-polariton waveguides - Gagnon, Guy (University of Ottawa (Canada), 2004)
A plasmon-polariton waveguide is investigated for its thermo-optic capability for the first time in the context of variable optical attenuators. The optical waveguide's metal core embedded into thermo-optic materials can be heated due to ohmic losses when current is injected through it. Hence, the optical and electrical function is agglomerated into the same waveguide layer. Heat changes the surrounding materials' refractive index and affects light propagation. The variable optical attenuator's response time was shown to be as fast as 50mus. The 8mum x 20nm metal waveguide achieves 19dB extinction ratio with 222 mW of electrical power consumption. Many other waveguide's characteristics were obtained experimentally and through thermal, electrical and optical modeling. The metal waveguide was used as a non-invasive, direct and accurate temperature sensor. Electromigration and electrostatic discharge were investigated as the waveguide's degrading mechanisms. A novel optical method to study thin metal films' degradation due to electromigration is suggested.
Keywords: Engineering, Electronics and Electrical.